Shifting Orientation in Competition from Profit to People Quality: Influence of Service Quality, Product, Satisfaction on Customer Loyalty of a Fastfood Restaurant in Jakarta - Fery, Fery; Sembel, Jacquelinda Sandra (Feedforward: Journal of Human Resource, 2021)
In fast-food industry, food quality and safety become pre-requisite to launch a fast-food restaurant. Thus, the players in this industry offer similar quality of food. This has caused a shift of the focus of competition in the industry from competing in the quality of product to the quality of human resources in serving customers. The aim of this study is to find out whether service quality, product, and satisfaction have any impact on customer loyalty. The study surveyed 30 respondents in the pre-testing and 170 respondents in actual data testing. SmartPLS3.2 software was used to process data, that was collected using questionnaire. Data processing was conducted using validity test, reliability test, multiple regression analysis and hypothesis testing. The test revealed that Service Quality is indeed an important variable to affect Customer Loyalty. The same result applied to Product and Satisfaction what also revealed positive effect on Customer Loyalty.